Willingness to be tested for a secondary cause of hypertension: a survey of the Australian general community - Lai, J.H.; Gwini, S.M.; Chen, G.; Long, K.M.; Russell, G.; Schlaich, M.P.; Stowasser, M.; Young, M.J.; Fuller, P.J.; Mori, T.A.; Wolley, M.; Reid, Christopher; et al. (WILEY, 2022)
Background: Primary aldosteronism (PA) represents the most common and potentially curable cause of secondary hypertension. However, PA is not commonly screened for, and up to 34% of patients who screen positive do not complete the full diagnostic process. This suggests that the diagnostic process may pose a barrier to patients and may contribute to the under-diagnosis of PA. Aims: To evaluate the willingness of the Australian general public to undergo testing for secondary causes of hypertension and identify enablers or barriers to testing from the patients' perspective. Methods: An online survey containing questions on knowledge and attitudes towards hypertension, willingness to be tested and enablers/barriers towards testing was distributed to the Australian community. Results: Of 520 adult respondents (mean age 50.4 years, SD 27.3 years; 28.8% hypertensive; 56.0% female), the majority of non-hypertensive and hypertensive respondents (82.7% vs 70.0%; P = 0.03) were willing to undergo testing for a secondary cause of hypertension that involved blood and urine tests. Greater knowledge of hypertensive risk modification strategies and complications was predictive of willingness to be tested, whereas age, sex, education level, geographic location, socio-economic status and cardiovascular comorbidities were not. The top three barriers to testing included fear of a serious underlying condition, lack of belief in further testing and increased stress associated with further testing. Conclusion: A high proportion of patients are willing to engage in testing for a secondary cause of hypertension. Education about the risks associated with hypertension and the testing process may overcome several barriers to testing.